1995
DOI: 10.1002/ajim.4700280107
|View full text |Cite
|
Sign up to set email alerts
|

High frequency of metalworkers among patients with seminomatous tumors of the testis: A case‐control study

Abstract: Occupational analyses were conducted between 1971 and 1978 comparing 165 cases of testicular cancer in the Hannover region of Germany with 187 controls without neoplastic diseases admitted to the Hannover University Medical School during the same period. The results showed a significantly higher risk of metal workers developing seminomas and mixed seminomatous tumors compared to the controls (odds ratio 2.05; 1.17-3.58). There was a lack of risk for the nonseminomatous tumors as a whole group, and cases with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 40 publications
(14 reference statements)
3
25
0
Order By: Relevance
“…But the small prevalence of this subgroup and the occupational groups within it could not explain the risk seen for ''machinery fitters, machinery assemblers & precision instrument makers.'' Testicular cancer has been associated with various occupations including metal workers, farmers, textile workers, police officers, fire-fighters, sales and service managers, but findings were inconsistent across studies [Pearce and Howard, 1986;Rhomberg et al, 1995;Pollán et al, 2001;Stang et al, 2003]. The previously observed association with employment as a metal worker is corroborated by our study.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…But the small prevalence of this subgroup and the occupational groups within it could not explain the risk seen for ''machinery fitters, machinery assemblers & precision instrument makers.'' Testicular cancer has been associated with various occupations including metal workers, farmers, textile workers, police officers, fire-fighters, sales and service managers, but findings were inconsistent across studies [Pearce and Howard, 1986;Rhomberg et al, 1995;Pollán et al, 2001;Stang et al, 2003]. The previously observed association with employment as a metal worker is corroborated by our study.…”
Section: Discussionsupporting
confidence: 83%
“…Although many studies found positive associations between occupation and testicular cancer [Mills et al, 1984;Garland et al, 1988;Swerdlow and Skeet, 1988;Hayes et al, 1990;Marshall et al, 1990;Tarone et al, 1991;Van den Eeden et al, 1991;Davis and Mostofi, 1993;Rhomberg et al, 1995;Knight et al, 1996;Hardell et al, 1998;Fleming et al, 1999;Andersson et al, 2003;Walschaerts et al, 2007], no particular occupation has emerged as a clear risk factor [Garner et al, 2005]. Occupational exposure to several chemical agents including phthalates and pesticides were observed to be associated with testicular cancer and their endocrine disrupting potential was discussed as a possible mode of action [Ducatman et al, 1986;Levin et al, 1987;Haughey et al, 1989;Kristensen et al, 1996;Hardell et al, 1998;Fleming et al, 1999;IARC, 1999].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…[26][27][28] Exposure to electromagnetic fields has also been associated with development of testicular cancer, in particular with non-seminoma, 29 whereas excess seminomas have been found among metal workers. 30 Only one of the nine furnace workers with testicular cancer had died of the disease (during 1962-1990). Thus, in cancer mortality studies in other industrial groups an increased incidence of testicular cancers may have passed unnoticed.…”
Section: Discussionmentioning
confidence: 99%
“…Although many studies have found positive associations between occupation and testicular cancer, 6,[90][91][92][93][94][95][96][97][98][99][100][101][102][103][104] no occupation has emerged as a clear risk factor for this lesion. Occupational exposures to several chemical substances have also been associated with testicular cancer.…”
Section: Occupational Exposuresmentioning
confidence: 99%